An evaluation on the level of willingness among selected University of the Philippines Visayas Tacloban College (UPVTC) students to engage in network marketing business - Astorga, Joshua L.; Borata, Felix Gian L.; Borja, Erron J.; Caneja, Monica Mae O.; Pormon, Miah Maye M. (2017)
Currently, network marketing is the growing trend of business by directly selling their products to the customers based from personal referrals or door-to-door selling-making it attractive to individuals specifically the students who want to earn money. Given the context, the paper examined the willingness of engaging in network marketing businesses among the 122 students in UPVTC. Specifically, the paper initially described the costs and benefits of entering the business, the socio-demographic and economic profile and factors that attract or hinder students in joining. Data were collected through survey in March to April 2017. There were 99 students who reported that they are familiar with networking, however, only 76 are well knowledgeable about the business. Only two of the study participants were members of networking companies. Moreover, majority of the study participants (65.6%) are unwilling to engage in network marketing businesses considering that it is time consuming and it requires a lot of effort. In addition, students from UPVTC are unlikely to choose network marketing business as a career (75.8%). Multinomial logit regression was done to determine the factors that affect the willingness of students to engage in the said business. The regression showed that age is the most significant factor affecting their willingness. Other factors such as time cost, monetary cost and academic workload were also significant at 5 percent level of significance. The researchers recommend exploring more factors that could affect the decisions of the students, as well as widening the scope of the studies to other colleges.
Undergraduate thesis (BASS Economics) -- University of the Philippines, Tacloban.